Pengaruh Pembelajaran Kooperatif Tipe STAD Terhadap Peningkatan Hasil Belajar, Sikap Sosial, dan Motivasi Belajar - Dedek Andrian; Astri Wahyuni; Syarul Ramadhan; Fini Rezy Enabela Novilanti; Zafrullah (Jurnal Inovasi Matematika, 2020)
The purpose of this study was to determine the effect of cooperative learning of Student Team Achievement Division (STAD) type in improving students’ learning outcomes, social attitudes,and students’ motivation. This is a quasi-experimental study using control and experimental classes. The research instruments used in this study were tests and questionnaires. The data were analyzed by using Multivariate Analysis of Variants (MANOVA). Theresult of the analysis showed that there was a significant influence between the experimental class with cooperative learning of STAD type and the control class with conventional learning viewed from the learning outcomes, social attitudes, and motivation of the students. These results can be seen from the statistical value of Hotelling's Trace which was smaller than 0.05. Cooperative learning simultaneously could improve learning outcomes, social attitudes, and learning motivation of students of SMAN 1 Tebing Tinggi.